MAÞiR Trees - Språkbanken Text (University of Gothenburg, 2024)
Mathir Trees contains 5 manually annotated Old Swedish texts or text
fragments: 'Här sigx aff abotum allum skemptan mykla', a satirical text
about abbots; the first chapter of Äldre Västgötalagen, a 13th century
Västergötland provincial law; the first 20-something (edition) pages from
Pentateuchparafrasen, a paraphrase of the five books of Moses; the first
5 chapters (plus some fragments) of Östgötalagen, a 13th century
Östergötland provincial law; part 1 of Tungulus, Visio Tnugdali/Vision of
Tundale, the shorter version. The texts consist of more than 33 000
tokens and close to 2 500 sentences. The annotation is provided in PROIEL
XML files. The morpho-syntactic annotation in MAÞiR Trees follows the
Menotec guidelines and is part of the PROIEL family of annotation
guidelines/treebanks. Lemmatization is based on Söderwall's dictionary
and supplements. The resource was compiled as part of the Mathir project,
financed by the Marcus and Amalia Wallenberg Foundation, no. 2012.0146,
by Gerlof Bouma and Yvonne Adesam.

Mathir Träd innehåller 5 manuellt annoterade fornsvenska texter eller
textfragment: 'Här sigx aff abotum allum skemptan mykla', en satirisk
text om abbotar; första kapitlet av Äldre Västgötalagen, en lagtext från
1200-talet; de första ungefär 20 sidorna av Pentateuchparafrasen, en
parafrasering av moseböckerna; de första 5 kapitlen (samt några fragment)
av Östgötalagen, en lagtext från 1200-talet; del 1 av Tungulus, Visio
Tnugdali, den kortare versionen. Texterna består av mer än 33 000 token
och nära 2 500 meningar. Annoteringen finns i PROIEL-XML-filer. Den
morfosyntaktiska annoteringen i Mathir Träd följer Menotec-riktlinjerna
och är del av annoteringsriktlinjerna/trädbankerna inom PROIEL-familjen.
Lemmatiseringen bygger på Söderwalls ordbok och supplement. Resursen
sammanställdes inom projektet Mathir, finansierat av Marcus och Amalia
Wallenbergs Minnesfond, nr. 2012.0146, av Gerlof Bouma och Yvonne
Adesam.
MAÞiR Träd
Keywords: Language Technology (Computational Linguistics); treebank; historical; corpus; History; Historia; Natural Language Processing; Språkbehandling och datorlingvistik